Snoezelen in people with intellectual disability or dementia: A systematic review - Gemma Testerink; Annet ten Brug; Gerdine Douma; Annette van der Putten (Elsevier, 2023)
Background: Snoezelen focuses on multisensory stimulation in an adapted environment and was originally developed for people with severe and profound intellectual (and multiple) disabilities. Snoezelen has been used for many years with various target groups and for different purposes. Variation in its application has resulted in a lack of understanding of snoezelen's application characteristics and of how they may relate to effects. Objective: The aim of this review was to provide an overview of the application and effects of snoezelen in people with intellectual disability or dementia in order to analyse the relationship between application characteristics and effects. Design: A systematic review. Methods: Five databases were searched for snoezelen studies that took place in a specially adapted environment. The methodological quality of the included studies was assessed using the Mixed Methods Appraisal Tool. The application characteristics (that is, the stimuli used, environment, and support given) and the effects were extracted. Reported effects were categorized into different human functioning dimensions using the model of intellectual disabilities of the American Association on Intellectual and Developmental Disabilities. Results: In total, 62 studies involving people with intellectual disability (n = 30) or dementia (n = 32) were included. An overview of snoezelen used in other target groups (n = 24) is provided as supplementary material. Details on the application of snoezelen were often lacking. A total of 10 application characteristics (for example, frequency, role of the support person) were extracted. All studies reported the presence of a support person (n = 62; 100%). Effects were found in all five human functioning dimensions. The most-reported effects (61.3% overall) related to mental health, such as a reduction in challenging behaviour and improved mood. In a minority of studies (n = 10, 16.1%), effects on the support person were also reported. Due to limited details about the application of snoezelen and the large variation in measured effects, analysing the relationship between these was impossible. Conclusions: The majority of studies lacked details on application characteristics during snoezelen. Reported effects varied, although most related to mental health. Future research should analyse in detail the relationship between application and effects.